Stemness and EMT profiles shift in xenografts derived from cisplatin-sensitive and cisplatin-tolerant ovarian cancer cells - Alena Mrkvicova; Marcela Slavickova; Eva Peterova; Lucie Melounkova; Helena Parova; Radim Havelek; Anna Krejcova; Renata Kohlerova; Jana Nekvindova; Petra Kazimirova; Milena Hajzlerova; Tomáš Rozkoš; et al. (PLoS ONE, 2026)
The transcriptional alterations underlying epithelial-to-mesenchymal transition (EMT) in chemoresistant ovarian cancer remain a matter of debate, with emerging evidence pointing to tumour cell plasticity and subclone reprogramming. In this study, we developed a cisplatin-tolerant ovarian cancer model by treating the cisplatin-sensitive OVCAR-3 cell line with a single dose of cisplatin, generating the OVCAR-3 CP variant. These cisplatin-tolerant cells exhibited distinct EMT-related changes at both transcriptomic and protein levels, potentially regulated by epigenetic mechanisms. EMT profiling revealed that OVCAR-3 CP cells did not display a pronounced mesenchymal phenotype but rather retained epithelial characteristics and showed elevated expression of ALDH3A1 . In contrast, the parental chemosensitive OVCAR-3 cells expressed canonical mesenchymal markers ( CDH2, VIM, ZEB1/2, SNAIL, SLUG ) and lacked stemness marker expression. Upon xenografting, both OVCAR-3 and OVCAR-3 CP cells demonstrated phenotypic plasticity, with parental OVCAR-3 xenografts acquiring EMT-like features resembling to those observed in cisplatin-tolerant tumours. These findings suggest a decoupling of EMT from cisplatin-tolerance and instead underscore a stronger association between stemness traits and cisplatin tolerance. Our data further indicate that xenografting can induce significant cellular reprogramming. Comprehensive characterization of ovarian cancer cell-derived xenograft is therefore essential, as they represent a valuable translational platform for investigating therapy adapted ovarian cancer cells.